Nike (Awaous melanocephalus) Fishery and Mercury Contamination in the Estuary of BoneBolango River - Aziz Salam; Femy M Sahami; Citra Panigoro (Journal Omni-Akuatika, 2016)
Nike fish (Awaous melanocephalus) is a tiny-kind of fish harvested lunar-monthly in the estuary of BoneBolangoRiver in the City of Gorontalo. The fishing activity is showing steady increase recently as thecommodity finds its way to the international market. Fishermen are putting more efforts by escalating thecatching capacity of their gears. Meanwhile, mercury used by the artisanal and small-scale gold mining(ASGM) in the headwaters for amalgamation put another aspect to the A. melanocephalus  fishery whenit wasted into the river down to the estuary. This paper describes A. melanocephalus  fishery and thethreat of mercury contamination in the habitat and the fish itself. Field research was conducted in theestuary of Bone-Bolango River to observe the technology and methods of A. melanocephalus  fishing.Samples of water and fish were taken for mercury content examination with Atomic AbsorptionSpectrophotometer (AAS). Secondary data on production and distribution were obtained fromgovernment offices. The result showed that the water and A. melanocephalus  samples contain mercuryat levels exceeding the quality standards determined by government. Keywords: nike, mercury, food security, sustainable fishery